2022
DOI: 10.1177/08982643221085408
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement and Sleep Among Older African Americans

Abstract: Objective: This study sought to determine whether religious involvement is associated with sleep quality in a nationally representative sample of older African Americans. Methods: The analytic sample included African American respondents aged 55+ from the National Survey of American Life-Reinterview ( N = 459). Religious involvement variables included service attendance, reading religious texts, watching religious television programs, listening to religious radio programs, prayer, and subjective religiosity. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…32 Religious involvement among African Americans has also been associated with fewer depressive symptoms, greater life satisfaction, and sleep maintenance. [33][34][35] In addition, religious engagement has been associated with lower CRP in African Americans 36 and potentially buffering the adverse effects of perceived racism on inflammatory markers. 37 Notably, the Jackson Heart Study found a significant association between religiosity/spirituality and ideal cardiovascular health among men, but not women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Religious involvement among African Americans has also been associated with fewer depressive symptoms, greater life satisfaction, and sleep maintenance. [33][34][35] In addition, religious engagement has been associated with lower CRP in African Americans 36 and potentially buffering the adverse effects of perceived racism on inflammatory markers. 37 Notably, the Jackson Heart Study found a significant association between religiosity/spirituality and ideal cardiovascular health among men, but not women.…”
Section: Discussionmentioning
confidence: 99%
“…In the Jackson Heart Study, religious/spiritual practices (eg, private prayer, attendance at services) were associated with better cardiovascular health across multiple indicators including physical activity, diet, smoking, and blood pressure 32 . Religious involvement among African Americans has also been associated with fewer depressive symptoms, greater life satisfaction, and sleep maintenance 33-35 . In addition, religious engagement has been associated with lower CRP in African Americans 36 and potentially buffering the adverse effects of perceived racism on inflammatory markers 37 …”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al’s article investigates the link between religious involvement and sleep quality among older African Americans. Their research focused on organizational, nonorganizational, and subjective aspects of religious involvement and found that watching religious television programs was associated with more restless sleep.…”
Section: Introductionmentioning
confidence: 99%